The procedural position of the mayor of a town with district rights during proceedings dealing with the special road law considerations with respect to the resolution adopted by seven judges of the supreme administrative court on 16th February 2016, I OPS 2/15 - Nowakowski-Węgrzynowski, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The act on special conditions for preparing and implementing public road investment (the so called special road act) has always caused problems as far as its interpretation goes. One of these problems is the issue of the procedural position of mayors of towns with district rights who are present in the proceedings conducted according to the above mentioned act. On one hand, they constitute the competent authority to conduct the proceedings. On the other hand, they are a party to the very same proceedings. Because there is no clear regulation on the part of the legislator there can be observed varied solutions as to how to conduct proceedings under the special road law. An analysis of these solutions may lead one to a conclusion that some of them are relatively correct, or at least their legal and logical justification is possible. However, in a country abiding by law such a situation must not be tolerated. That is why, petitions advocating changes to the special road law must be delivered to the legislator. It is also important that we consider which of the solutions implemented by public administration offices is most correct and desirable.